Biomimetic aligned nanofibrous dressings containing cell-selective polymer enhance diabetic wound regeneration - Erfan Rezvani Ghomi; Venkatesh Mayandi; Vijila Chellappan; Nileshkumar Dubey; Kottaiswamy Amuthavalli; Rasoul Esmaeely Neisiany; Veluchamy Amutha Barathi; Navin Kumar Verma; Rajamani Lakshminarayanan; Seeram Ramakrishna (Materials & Design, 2024)
Diabetic ulcers remain a significant challenge in wound care due to loss of epithelial cell migration. Aligned nanofibrous scaffolds mimicking the skin's extracellular matrix (ECM) are promising candidates for diabetic wound healing. In this study, a composition of poly(ε-caprolactone), gelatin, and dopamine-containing varying amounts of ε-polylysine (ε-PL) was electrospun to prepare aligned nanofiber wound dressings (ANFDs). We then investigated the morphological, physicochemical, mechanical, and biological properties of fabricated ANDFs. The presence of ε-PL confers bactericidal properties while promoting epithelial and fibroblast adhesion, proliferation, and migration, confirming its cell selectivity. The clinical importance of the ANFDs was then demonstrated in a mice model of full-thickness diabetic wounds. The results confirm that ANFD treatment resulted in a higher rate of wound closure in the linear range of wound closure than wounds treated with silver dressings. Taken together, these results suggest the potential of antimicrobial ANFDs for the treatment of diabetic wounds.